SOME NEW SEQUENCE-SPACES DEFINED BY A MODULUS FUNCTION - NURAY, F; SAVAS, E (Indian Nat Sci Acad, 1993)
In this paper we introduce and examine some properties of three sequence spaces defined using a modulus function.